Performance analysis of a solar-only gas micro turbine, with mass flow control. (September 2017) - Rovense, F.; Amelio, M.; Scornaienchi, N.M.; Ferraro, V.
Abstract: Micro gas turbine applications in concentrating solar field systems is already on industrial stage. The peculiarity of these systems is the possibility to use fossil fuels when solar power source is lacking. It is preferable that the system works in solar-only mode for long time; however, owing to the efficiency loss which occur for low radiation levels, a fuel integration is necessary. This work presents a system which allows to operate with constant efficiency, without the use of fuel for over one fifth of the nominal power rate. It is based on a regenerated micro gas turbine in closed loop configuration. The proposed system includes the solar tower, the heliostats field, the regenerator and a low temperature heat exchanger which cools the working fluid. Finally, two more devices, for the actuation of the proposed control are included: an auxiliary compressor and a bleed valve. The use of air as working fluid has been analyzed, with different values of the base cycle pressure (inlet pressure of the main compressor), which are needed for varying the mass flow flowing in the system. The control of the mass flow rate is mandatory to regulate the gas turbine power, by keeping almost constant the maximum temperature of the thermodynamic cycle when the incident solar radiation changes. In particular, the auxiliary compressor admits fresh air in the cycle when the thermal power received by the sun increases, while the bleed valve discharges it in the atmosphere, when the thermal power decreases. Therefore, the thermodynamic cycle is unchanged and guarantees constant net system efficiency for all the operations conditions. Particular attention is given to the receiver thermal incident flux, heliostat field and solar tower design. The current results are compared with the annual efficiency and energy production of an existing plant in hybrid configuration (solar-fuel).The analysis has been carried out on a commercial gas turbine having a power of 100 kW, sited on Seville town. For the heliostat field analysis, the open source code Solar PILOT has been used, while for the entire plant the code Thermoflex has been employed.